Pemanfaatan Ekstrak Kulit Pisang Sebagai Green Inhibitor Dengan Metode Maserasi Dalam Upaya Mengendalikan Korosi Pada Baja ASTM 36 - Harfiah Faradila; Komalasari Komalasari; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Corrosion is the interaction of materials with the environment that result in damage to material and the environment. a method of restricting the occurrence of corrosion processes with inhibitors. An organic inhibitor that is an inhibitor that is made from natural materials available in nature. Extract of banana peels contains tannin compounds that can prevent corrosion. The purpose of the research was to determine yield and extract of banana peels maceration method, determine the rate of steel corrosion using inhibitor corrosion, and determine the influence of the concentration of inhibitor, corrosion, media and contact time variation of the rate of corrosion. This research began with extract of banana peels is done by the method of contact during the maceration time with the 7hari. Then proceed with the contact of steel corrosion on media that is HCl and NaOH concentration extract with 0 gr/L and 1 g/L on the contact time of 12, 24, 48, 72 hours. The results of this study showed the greater the concentration of the inhibitor of the smaller banana peels extracts the rate of corrosion.Keywords: banana peels, carbon steel ASTM 36, corrosion rate, green inhibitor.